2021
DOI: 10.1111/bcp.14999
|View full text |Cite
|
Sign up to set email alerts
|

Intradermal lipopolysaccharide challenge as an acute in vivo inflammatory model in healthy volunteers

Abstract: Whereas intravenous administration of Toll-like receptor 4 ligand lipopolysaccharide (LPS) to human volunteers is frequently used in clinical pharmacology studies, systemic use of LPS has practical limitations. We aimed to characterize the intradermal LPS response in healthy volunteers, and as such qualify the method as local inflammation model for clinical pharmacology studies.Methods: Eighteen healthy male volunteers received 2 or 4 intradermal 10 ng LPS injections and 1 saline injection on the forearms. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…In line with this, glucocorticoids may impair the capacity of neutrophils to extravasate into inflamed tissue, 7 but in the present study the recruitment of neutrophils was unaffected (Figure 4a). Neutrophils, as we have already shown during the earlier characterization of the intradermal LPS model, are the first cells to arrive in response to LPS, 5,6 and it is known that neutrophils play a central role in orchestrating the acute immune response. 17 The fact that we did not observe a reduction in neutrophil infiltration but did observe a reduction of all other immune cell subsets gave rise to our hypothesis that corticosteroid pretreatment did not affect the capacity of stromal cells and local immune cells to initiate neutrophil attraction but did lead to a reduced capacity of arriving neutrophils to further drive the acute immune response.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…In line with this, glucocorticoids may impair the capacity of neutrophils to extravasate into inflamed tissue, 7 but in the present study the recruitment of neutrophils was unaffected (Figure 4a). Neutrophils, as we have already shown during the earlier characterization of the intradermal LPS model, are the first cells to arrive in response to LPS, 5,6 and it is known that neutrophils play a central role in orchestrating the acute immune response. 17 The fact that we did not observe a reduction in neutrophil infiltration but did observe a reduction of all other immune cell subsets gave rise to our hypothesis that corticosteroid pretreatment did not affect the capacity of stromal cells and local immune cells to initiate neutrophil attraction but did lead to a reduced capacity of arriving neutrophils to further drive the acute immune response.…”
Section: Discussionmentioning
confidence: 82%
“…Secondly, exposure to systemic LPS leads to a prolonged state of immunological hyporesponsiveness to LPS due to innate memory which hampers the possibility of rechallenging the same individual 3,4 . We and others have published a local inflammatory challenge with intradermal LPS 5,6 . In our comprehensive characterization we showed that intradermal administration of 5 ng of LPS induces a transient local inflammatory response, characterized by an increase in local perfusion, heat, erythema, immune cell attraction, and cytokine production 6 .…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…For example, obesity is hypothesized to reduce TT and SHBG concentrations via several proposed mechanisms, including inflammation. Therefore, an interventional study could be conducted using an intradermal lipopolysaccharide (LPS) challenge, with a similar study design to Buters et al, (2022), which would induce inflammation. TT and SHBG concentrations could be tested at various timepoints after administration, and perhaps compared with a placebo intradermal challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Skin erythema was quantified using multispectral imaging (Antera 3D®, Miravex), as described in detail before. 22,23,25 The multispectral camera creates a closed chamber of 25 cm 2 for image capture with standardized lighting and distance. A region of interest of 4 mm in diameter was defined and kept analogous with all analysed images.…”
Section: Clinical Imaging: Erythema Planimetry and Morphologymentioning
confidence: 99%